Unambiguous Events and Dynamic Choquet Preferences - Adam Dominiak; Jean-Philippe Lefort (University of Heidelberg, Department of Economics, 2009)
This paper explores the relationship between dynamic consistency and the existing notions of unambiguous events for Choquet expected utility preferences. A decision maker is faced with an information structure represented by a filtration. We show that the decision maker's preferences respect dynamic consistency on a fixed filtration if and only if the last stage of the filtration is composed of unambiguous events in the sense of Nehring (1999). Adopting two axioms, conditional certainty equivalence consistency and constrained dynamic consistency to filtration measurable acts, it is shown that the decision maker respects these two axioms on a fixed filtration if and only if the last stage of the filtration is made up of unambiguous events the sense of Zhang (2002).
urn:nbn:de:bsz:16-opus-98382
Keywords: D81; 330; Choquet expected utility; unambiguous events; filtration; updating; dynamic consistency; consequentialism; Erwartungsnutzen; Asymmetrische Information; Entscheidung unter Risiko; Wahrscheinlichkeitsrechnung; Theorie